Faktor Risiko Kejadian Schistosomiasis di Dataran Tinggi Lindu Kabupaten Sigi Sulawesi Tengah - Akbar, Hairil (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2018)
Schistosomiasis, known as snail fever is a parasitic disease caused byinfection with trematode worms of the genus Schistosomajaponica Sp (blood flukes) that live in the mesenterica vein or veins of the bladder. The purpose of this study was to determine epidemiological determinants in the incidence of Schistosomiasis in Lindu Plateau, Sigi Regency. The study applied observational analytic with case control method. The sample size used in this study consisted of 82 people representing 41 people for cases and 41 people for controls obtainedwith Simple Random Sampling. The result indicated that there were significantÂ influence of the history of Schistosomiasis, with p value 0,000 (p < 0,05) and the utilization of health programs with p value of 0,020 (p < 0,05). While variable jobs p value 0,165 (p > 0,05), income p value 1,000 (p > 0,05) there is no influence on the incidence of Schistosomiasis. Based on the findings above, it can be inferred that the prevalence of the Schistosomiasis was still high, these diseaseÂ is closely related to the behaviors or habits of the community.Keywords: Community Behavior, Lindu, Schistosomiasis,